Riesgo de diabetes gestacional en mujeres atendidas en el servicio de ginecología-obstetricia del Hospital Clínica San Agustín - Bravo Encalada, Christian Rafael (2020)
Developing gestational diabetes attributable to a hyperglycemic state during pregnancy is one of the risk factors that affects both the mother and the fetus. The purpose of this study was to identify risk factors for developing gestational diabetes; use of the O'Sullivan test to check blood glucose parameters; and to establish the relationship of risk factors with respect to the O'Sullivan test. This study was conducted on pregnant women attended by the gynecology-obstetrics service at the Hospital Clínica San Agustín, during the period July-December 2018. The research was carried out using a quantitative cross sectional approach on a population sample of 116 pregnant women over 18 who attended the aforementioned service; obtaining as a result: that the mestizo age group of 25 to 34 years prevailed in the study population, the most concurrent risk factors were obesity (21.6%) and the family history of type II diabetes mellitus (19.8 %) in relation to high risk factors; and overweight (48.3%) corresponding to the medium risk factors. About a third of the population tested positive for said test (31.9%), taking into account that the risk factors for the said positive test were mixed ethnicity (31.8%), followed by being overweight (19.8%) and a family history of type II diabetes mellitus (11.2%) confirming that these risk factors predispose pregnant women to developing gestational diabetes. Key words: Gestational diabetes, risk factors, O'Sullivan test, insulin resistance, obstetric complications